The Effect Of Car, Bopo Ratio, And Npl Ratio On The Profitability (Roe) Of Foreign Exchange Business In Indonesia (2012-2016 Period). - Fauzi isnaen; Fauzan akbar (Journal Of Social Science (JoSS), 2022)
Banking financial performance comes from several factors, namely that it is very important for a bank's capital to be achieved within the limits set by Bank Indonesia. The ratios that are quite significant in banking are the capital adequacy ratio (CAR), the BOPO Ratio, OJK explained that efficiency continues to be encouraged for banks so that they are able to reduce operational costs to operating income, as well as the ratio of non-performing loans or non-performing loans (NPL). . This study emphasizes the effect of CAR, BOPO ratio, and NPL ratio on the profitability of foreign exchange BUSN in Indonesia. Researchers used a sample of 35 banks for the 2012-2016 period, with secondary data types and quantitative analysis methods, statistical calculations in this study using Eviews 8 software. and NPL have no significant effect on ROE. The ratio of CAR, BOPO, and NPL statistically significant effect on bank profitability.